Nickel catalytic graphitized porous carbon as electrode material for high performance supercapacitors. (15th April 2016) - Wang, Keliang; Cao, Yuhe; Wang, Xiaomin; Kharel, Parashu Ram; Gibbons, William; Luo, Bing; Gu, Zhengrong; Fan, Qihua; Metzger, Lloyd
Abstract: Whey-protein-derived nitrogen-doped porous carbon has been prepared by preliminary carbonization at 400 °C and final KOH activation at 700 °C combined with catalytic graphitization. Physical characterization indicated that the nitrogen-doped activated electrode material had a large specific surface area (2536 m 2  g −1 ) and plenty of interconnected cavities, which greatly improved the performance of supercapacitors. Electrochemical measurements demonstrated that the as-prepared activated electrode material had exceptionally high capacitance of 248 F g −1 at charge/discharge current density of 0.1 A g −1 . Moreover, the prepared supercapacitors exhibited ideal capacitive behavior with nearly no capacitance loss in 6 mol L −1 KOH at different charge/discharge current densities ranging from 0.1 to 5 A g −1 after 1000 charge/discharge cycles. The derived energy density was 12.4 Wh kg −1 at a power density of 495 W kg −1 under operational conditions. These results suggested that the whey-protein-derived porous carbon is a promising supercapacitor electrode material. Graphical abstract: Highlights: Porous N-doped carbon was prepared by KOH activation under Ni catalysis. High specific surface area, low cost, and good electrical conductivity. High specific capacitance of 248 F g −1 at 0.1 A g −1 and excellent cyclic stability.